Development Of A High-Throughput Assay For Screening Plant Extracts That Can Extend The Chronological Life Span Of Yeast Saccharomyces Cerevisiae - Mandy Kwong, Mun Yee (2019)
Bioactive compounds are produced in different parts of a plant, and the compounds can be extracted as plant extracts (PEs). Some bioactive compounds have pharmacological properties such as antioxidant and lifespan-extending activities on organisms in vitro and in vivo. The budding yeast Saccharomyces cerevisiae is a model organism for studying the mechanisms of ageing because yeast shares conserved pathways to higher eukaryotes. The chronological life span (CLS) of yeast is defined as the capacity of cells to remain viable in a non-dividing state. In this study, leaf extracts of of Manihot esculenta, Wodyetia bifurcata and Tabernaemontana divaricata were found to extend yeast CLS. A high-throughput 96-well based CLS assay was developed to enable quantitative screening of many PEs simultaneously to identify plant extracts with yeast CLS-extending activity.